2012
DOI: 10.1080/1943815x.2012.696548
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the findings from measurements of halogenated compounds at Gosan (Jeju Island, Korea) quantifying emissions in East Asia

Abstract: With increased economic growth in East Asia, regional emissions of many anthropogenic halogenated compounds now constitute a substantial fraction of the global totals. Here, we summarize recently reported findings from measurements of a wide range of chlorofluorocarbons (CFCs), hydrochlorofluorocarbons (HCFCs), hydrofluorocarbons (HFCs), perfluorocarbons (PFCs), sulfur hexafluoride (SF 6 ), and other halogenated compounds at Gosan (Jeju Island, Korea) within the advanced global atmospheric gases experiment (AG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…at the southwestern tip of Jeju Island, South Korea (see Fig. 1), is ideally located to monitor regional background mole fractions of atmospheric trace gases due to minimal influence of local anthropogenic pollution sources and the strong pollution outflows from China, Korea, and Japan in East Asia (Kim et al, 2012;Li et al, 2011Li et al, , 2014Park et al, 2018).…”
Section: Instrumentation and Measurement Datamentioning
confidence: 99%
See 1 more Smart Citation
“…at the southwestern tip of Jeju Island, South Korea (see Fig. 1), is ideally located to monitor regional background mole fractions of atmospheric trace gases due to minimal influence of local anthropogenic pollution sources and the strong pollution outflows from China, Korea, and Japan in East Asia (Kim et al, 2012;Li et al, 2011Li et al, , 2014Park et al, 2018).…”
Section: Instrumentation and Measurement Datamentioning
confidence: 99%
“…Unlike most other ODSs, CH 3 Br has both natural and anthropogenic sources. The principal natural emission sources are the ocean (Hu et al, 2012), salt marshes (Montzka et al, 2011), wetlands (Lee-Taylor and Holland, 2000), fungi (Lee-Taylor and Holland, 2000;Lee-Taylor et al, 2001), and plants such as mangroves or shrubs (Rhew et al, 2001;Manley et al, 2007). Anthropogenic emission sources include fumigation (Carpenter et al, 2014), agricultural and biofuel biomass burning (Andreae and Merlet, 2001), and the rapeseed industry (Gan et al, 1998;Mead et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Observations from HFD (Arnold et al, 2019), BSD 10 were found at the CEDA data base (CEDA, 2023), and measurements for ZEP (2005)(2006)(2007)(2008)(2009)(2010) were found at the EBAS database (Tørseth et al, 2012). For the observations at BIK (Popa et al, 2010), BRM (Rust et al, 2022), GSN (Kim et al, 2012), and HAT (Saikawa et al, 2012) we refer to E. Popa <epopa2@yahoo.com>, S. Reinmann <stefan.reimann@empa.ch>, S. Park <sparky@knu.ac.kr>, and T. Global Air Sampling Network (Lan et al, 2023;Dlugokencky et al, 2020). For APB and NAT, INPE collected the samples, and the analysis was done together with NOAA/GML.…”
Section: S2 Supplementary Tablesmentioning
confidence: 99%
“…A number of recent studies based on atmospheric measurements and modeling have consistently shown a significant increase in the emissions of CFC-11 in East Asia. Emissions of CFC-11 in East Asia are of global significance, due to the large emissions from the fast-growing economies in this region. China, an Article-5 country under the MPA, is particularly important as it currently is the largest contributor to East Asia’s total CFC-11 emissions .…”
Section: Introductionmentioning
confidence: 99%